2021
DOI: 10.1038/s41385-020-00371-6
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia enhances ILC3 responses through HIF-1α-dependent mechanism

Abstract: Group 3 innate lymphoid cells (ILC3) have a prominent role in the maintenance of intestine mucosa homeostasis. The hypoxia-inducible factor (HIF) is an important modulator of immune cell activation and a key mechanism for cellular adaptation to oxygen deprivation. However, its role on ILC3 is not well known. In this study, we investigated how a hypoxic environment modulates ILC3 response and the subsequent participation of HIF-1 signaling in this process. We found increased proliferation and activation of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 49 publications
6
53
1
Order By: Relevance
“…Likewise, as reported by Fachi et al (2021) in RORγt-expressing ILC3s, HIF1α binds to the Rorc promoter but not the Tbx21 promoter and supports IL-22 and IL-17 expression (Fachi et al, 2021). In contrast to the investigation by Fachi et al (2021) that analyzed cytokine expression and HIF1α binding to the Rorc promoter by ChIP in the ILC3 cell line MNK3 after short-term exposure (up to 3 h) to near-anoxic conditions, we assessed Rorc and Tbx21 expression after 20 h of exposure to IL-12 and HIF1α binding to the Tbx21 promoter after 8-h incubation with IL-12 by Cut & Run in primary murine WT and HIF1α KO NKp46 + cells. Therefore, in addition to the different in vitro cell systems, the different stimuli and the duration of stimulation are likely to contribute to the observed discrepancies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Likewise, as reported by Fachi et al (2021) in RORγt-expressing ILC3s, HIF1α binds to the Rorc promoter but not the Tbx21 promoter and supports IL-22 and IL-17 expression (Fachi et al, 2021). In contrast to the investigation by Fachi et al (2021) that analyzed cytokine expression and HIF1α binding to the Rorc promoter by ChIP in the ILC3 cell line MNK3 after short-term exposure (up to 3 h) to near-anoxic conditions, we assessed Rorc and Tbx21 expression after 20 h of exposure to IL-12 and HIF1α binding to the Tbx21 promoter after 8-h incubation with IL-12 by Cut & Run in primary murine WT and HIF1α KO NKp46 + cells. Therefore, in addition to the different in vitro cell systems, the different stimuli and the duration of stimulation are likely to contribute to the observed discrepancies.…”
Section: Discussionsupporting
confidence: 72%
“…HIF-1α was also implicated in fostering the development of Th17 cells through direct transcriptional activation of RORγt (Dang et al, 2011). Likewise, as reported by Fachi et al (2021) in RORγt-expressing ILC3s, HIF1α binds to the Rorc promoter but not the Tbx21 promoter and supports IL-22 and IL-17 expression (Fachi et al, 2021). In contrast to the investigation by Fachi et al (2021) that analyzed cytokine expression and HIF1α binding to the Rorc promoter by ChIP in the ILC3 cell line MNK3 after short-term exposure (up to 3 h) to near-anoxic conditions, we assessed Rorc and Tbx21 expression after 20 h of exposure to IL-12 and HIF1α binding to the Tbx21 promoter after 8-h incubation with IL-12 by Cut & Run in primary murine WT and HIF1α KO NKp46 + cells.…”
Section: Discussionmentioning
confidence: 68%
“…mTOR signaling influences ILC3s in the intestine, leading to subsequent alteration in metabolic homeostasis. Notably, another study has reported that activation of ILC3s upon low oxygen challenge occurs via a HIF-1α-dependent mechanism instead of mTOR-signaling ( 146 ). P38 MAPK pathway also regulates the production of GM-CSF by ILC3s after activation of death receptor 3 (DR3) signaling ( 147 , 148 ).…”
Section: Ilcs In Intestinementioning
confidence: 99%
“…Although in that study, no effect of ox-LDL stimulation on ILC3s was observed, suggestive of other disease-specific effects of ox-LDL signalling on ILCs. ILC3s are regulated by hypoxia, acting via hypoxia inducible factor (HIF)-1α ( 78 ). Tissue hypoxia can be induced by, and contribute to CVDs ( 79 ).…”
Section: Ilcs and Cvd Pathogenesismentioning
confidence: 99%